Solve for x:
-2 – 8= -4x – 23


i
submit answer
submit answer

Answers

- 2 + 3x = 46 \\ 3x = 46 + 2 \\ 3x = 48 \\  \frac{3x}{3}  =  \frac{48}{3}  \\ x = 16

Answer D

1.A

2.C

3.B

4.B

Step-by-step explanation:

1   is   a

2   is   b

3   is  b

hope   it   helped

5.4


Step-by-step explanation: Isolate the variable by dividing each side factors that dn't dontain the variable.

Hope this helps! :) ~Zane

1) p=3

2)t=-7

3)x=15

4) x=7

Step-by-step explanation:

1) Apply distributive property:

2(p+ 5) = 16\\2p+10=16

Subtract 10 from both sides of the equation and then divide both sides by 2:

2p+10-10=16-10\\\frac{2p}{2}=\frac{6}{2}\\p=3

2) Apply distributive property:

-3(t + 1) = 18\\-3t -3= 18

Add 3 to both sides of the equation and then divide both sides by -3:

-3t -3+3= 18+3\\\frac{-3t}{-3}=\frac{21}{-3}\\t=-7

 3) Apply distributive property:

-\frac{2}{5}(x+10)=-10\\\\-\frac{2}{5}x-4=-10

Add 4 to both sides of the equation:

-\frac{2}{5}x-4+4=-10+4\\\\-\frac{2}{5}x=-6

Multiply both sides by -\frac{5}{2}:

(-\frac{2}{5}x)(-\frac{5}{2}) =-6(-\frac{5}{2})\\\\x=15

4) Apply distributive property:

\frac{2}{3}(x-10)=-2\\\\\frac{2}{3}x-\frac{20}{3}=-2

 Add \frac{20}{3} to both sides of the equation:

\frac{2}{3}x-\frac{20}{3}+\frac{20}{3}=-2+\frac{20}{3}\\\\\frac{2}{3}x=\frac{14}{3}

Multiply both sides by \frac{3}{2}:

(\frac{2}{3}x)(\frac{3}{2})=(\frac{14}{3})(\frac{3}{2})\\\\x=7

1) Is A- x < -3, or x> 5 (d=cant put the line under the second one) 
2) C- 25<*with line under* x >with line under*30 Because its between 25, so must be more, and 30, so has to be less than 30
3)?
4)?
                              
-10 < n < 85/4 < x ≤ 6

Step-by-step explanation:

1. Subtract 9:

  -10 < n < 8

__

2. Add 12, then divide by 8:

  10 < 8x ≤ 48

  10/8 < x ≤ 6

  5/4 < x ≤ 6 . . . . . with the fraction reduced

The rules of equality allow us the do these operations, provided that we do them to all parts of the compound inequality. That is, when we say "subtract 9", we mean ...

  -1 -9 < 9 +n -9 < 17 -9

This simplifies to the inequality we show above:

  -10 < n < 8

(1).Factor the expression: 15n- 18
answer
B:3(5n-6)

(2).solve for x:
-2.3(x-1.2) = -9.66
-2.3x  +2.76 = -9.66
-2.3x = -9.66 - 2.76
-2.3x = -12.42
      x = 5.4

answer is x = 5.4

I don't see any answer above matched.
I believe it’s X= -13 over 4

x = -3.25

Step-by-step explanation:

- 2 - 8 = - 4x - 23

- 2 - 8 + 23 = - 4x

13 = - 4x

13 / 4 = -x

3.25 = -x

-3.25 = x



Do you know the answer?

Other questions on the subject: Mathematics

13step-by-step explanation: divide the cost of the total of sodas you bought by the cost of one soda, for example: $24.57 divided by $1.89 is 13 which means you bought 13 sodas...Read More
1 more answers
Mathematics, 21.06.2019, JesuGranger
B. because the 7 represents "seven times", x represents "a number", 12 represents "plus twelve", and -4 represents "minus four"...Read More
1 more answers
Mathematics, 21.06.2019, mohd591
the most boring ever writtenstep-by-step explanation: i am writing something. yes, i plan to make it the most boring thing ever written. i go to the store. a car is parked. many ca...Read More
1 more answers
Mathematics, 21.06.2019, natjojo0512
answerfalseexplanationthese practices describe the manner the land use outcome is attained. land management methods implemented by corporations are a mandatory because they are a d...Read More
2 more answers